Resilience and regions: Building understanding of the Metaphor - Rolf Pendall; Kathryn A. Foster; Margaret Cowell (University of California, Institute of Urban and Regional Development (IURD), 2007)
In this paper, we review literature that explains and extends the meaning of resilience across several fields: ecology, psychology, economics, disaster studies, geography, political science and archeology. For metropolitan regions, the review suggests that we must proceed with caution and precision if we choose to make resilience a guiding metaphor for planning and policy, as well as for understanding regional dynamics. Across these fields, there are several common themes that may or may not apply to all aspects of metropolitan economic, social, political, and environmental dynamics. The next part of the paper ties together these themes across the literatures; at the end of the paper, we return to pose some of the implications of the resilience metaphor for metropolitan regions. First, most analysis that employs the resilience metaphor presumes that the phenomenon of interest exhibits at least one equilibrium; the majority of the research begins, in fact, from the possibility of multiple equilibria, and explains how and why those equilibria become unstable. When we say that a person, society, ecosystem, or city is resilient, we generally mean that in the face of shock or stress, it either returns to normal (i.e., equilibrium) rapidly afterward or at the least does not easily get pushed into a new normal (i.e., an alternative equilibrium). Recent studies, however, have begun to move past the equilibrium view, shifting their focus from resting points to processes of adaptation. Second, and related to the first point, analysis using the resilience metaphor generally takes a systems perspective. Some factors internal to the system, and some external to it, tend to strengthen it; othersagain, both internal and externalcan place it under stress. Some literatures (e.g., psychology, disaster studies) tend to focus more on internal resources that strengthen the system under study and exogenous stresses that threaten it. A key idea arising from ecological studies, panarchy, helps overcome some of the determinism of such systems perspectives as functionalism in sociology; whereas other systems views tend to portray individual actions and interactions as pre-determined outcomes of larger structural forces, the panarchy view leads observers to expect interaction between structure and agents. Third, most, but not all, of the literatures tend to adopt at least partially the view that observed equilibria are path-dependent, that is, they are a consequence of cumulative decisions, often over a long time period, that shift a system from having a very open future to having increasingly predictable (or locked in) paths. The interest in path dependency is particularly high in fields that attempt to understand multiple equilibria and the persistence of sub-optimal ones; in any multi-equilibrium world, any of a number of sometimes apparently random events or actions can lead a system toward a particular equilibrium. Finally, work that uses resilience as a metaphor tends to take a long view, whether of individuals (e.g., personality in the transition from a stressed childhood to functional or dysfunctional adulthood) or of cities (e.g., long-term recovery after a disaster). This long perspective tends to reinforce the first three points. Over the long run, an observer will often observe or impute one or more periods of stability amidst change at some level of function for the phenomenon of interest, reinforcing the belief in equilibrium. This is even truer if the analyst's attention is shaped by the resilience metaphor in ways that encourage her to look for equilibria. As a practical matter, furthermore, the analyst must bound the phenomenon of study (city, ecosystem, person) in ways that encourage her to view that phenomenon as having a persistent internal logic; that is, the phenomenon isn't just a social or political process or a series of unconnected events but is, rather, a system.
Keywords: 330